2022
DOI: 10.7880/abas.0220125a
|View full text |Cite
|
Sign up to set email alerts
|

Hot market (Abenomics) impact on the time to IPO

Abstract: This study examines how the performance of startups during the time period up to their initial public offering (IPO) is affected by the macro environment, a topic that has not been given much consideration to date. Taking the end of 2012 (the beginning of Abenomics), when Japan's economic environment shifted to a hot market, as the transition point, we analyzed companies that did IPOs in terms of such variables as the target market, the attributes of the companies in the sample (type of entrepreneurship), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The study found that the average time from entrepreneurship to IPO is relatively long for companies operating in a favorable economic environment. This may be because the favorable economic environment and improved business conditions have stimulated startups that have been taking a wait-and-see attitude (Ichikohji et al, 2022). Its purpose is to avoid information asymmetry in the IPO market, ensure the information disclosure of 2.…”
Section: Ipo Offering Mechanismmentioning
confidence: 99%
“…The study found that the average time from entrepreneurship to IPO is relatively long for companies operating in a favorable economic environment. This may be because the favorable economic environment and improved business conditions have stimulated startups that have been taking a wait-and-see attitude (Ichikohji et al, 2022). Its purpose is to avoid information asymmetry in the IPO market, ensure the information disclosure of 2.…”
Section: Ipo Offering Mechanismmentioning
confidence: 99%